Determine the prevalence and fluoroquinolone resistance pattern of Escherichia coli ST131 among clinical isolates from vaginitis patients - Noor Ismeal Nasser; Mohammed Sabri Abdul-Razzaq; Nadia M. Al-Hili (Medical Journal of Babylon)
Abstract Background: The most interesting lineage of Escherichia coli is the sequence type 131 (ST131), a pandemic clone that is responsible for the high incidence of E. coli infections outside the intestine; in addition, it contributes to the global dissemination of multiantibiotic resistance. Aims: To determine the prevalence of E. coli st131, along with their fluoroquinolone resistance patterns and their phylogenetic background. Materials and Methods: A total of 150 high vaginal swabs were taken from female patients with aerobic vaginitis and were screened for the isolation and identification of E. coli ST131 using polymerase chain reaction technology that targets ST131-specific sequence polymorphisms in both the mdh and gyrB genes. An antibiotic sensitivity test was performed to determine resistance patterns. Results: Twenty-seven (18%) E. coli isolates were obtained from women with aerobic vaginitis, including 11 (40.7%) isolates belonging to sequence type 131. Phylogenetic analysis showed that the majority belonged to phylogroup B2 (90.9%), and one isolate belonged to phylogroup B1 (9.09%). All the isolates were resistant to ciprofloxacin and norfloxacin, and levofloxacin, whereas they were all sensitive to gatifloxacin and moxifloxacin. Conclusions: The presence of E. coli ST131 among E. coli isolates from patients with aerobic vaginitis, and the confirmation of their high resistance to most fluoroquinolones included in this study reflect their ability to adapt to different sites, which increases their risk as a pathogen.